The Transfer Pattern of Culture, Customs, Belief of Birth, Old Age, Sickness and Death Effected the Mutual Support in the Community of Wat Kalaya District, Thonburi Amphur, Bangkok Metropolitan - Permphol, Wongsakorn (Journal of International Buddhist Studies, 2016)
The research purposed to study the pattern of mutual support, the transfer pattern of culture and the relevant factors of the pattern of mutual support in community. The research method was mixed method research. The sampling group was the people living at Wat Kalaya District totaling 1,470 persons and 320 persons of the sampling groups were selected by table. The sampling method was Stratified Quota Random sampling which were 6 communities including Wat Kalaya Community, Wat Prayoonrawongsawat community, Rong Klam Community, Kudee Chin Community, Bupparam Community and Tonson mosque and 3 religious (Buddhism, Christianity and Islam). The research tool was questionnaires separated into 5 rating scale with Alpha value equaled .948 and the qualitative research by the techniques of conversation focus groups emphasizing the leaders of religious and communities and the structural questionnaires for data collection. The data analysis applied the Content Analysis and the quantitative data analysis applied the statistical analysis i.e. Basic statistics, Multiple Regressions of both total and Stepwise type. The research result found that 1. The first looks at each other in the community as a whole. At a high level (mean = 3.65) BY aspects sacrifice (review) at a high level (mean = 3.64 Communications (Piya verbal) at a high level (mean = 3.63) in practice. benefits (Guerin Jariyawiroj) at a high level (mean = 3.66) and social practice (the Manat eye) at a high level (mean = 3.68). 2. The transfer pattern of culture in overall was good level (average value = 3.66). It had 6 indicators: 1) Learning 2) Culture change by the time in community 3) Culture transfer from one generation to next generation in community 4) Instruction of symbolic system of community to the next generation 5) Observation behavior 6) Learning procedure of children from their parent’s instruction. All were the important predicators of mutual support pattern with (ß) .232, .193, .134, .168, .179 and .170 respectively and percentage of predictors = 57.3. 3. The relevant factors of mutual support character in community found that 1) The persons who had different education would have the different mutual support in community. 2) The persons who had different occupations would have the different mutual supports in community. 3) The persons who had different religions would have different mutual support in community and 4) The persons who had different transfer would have different mutual support in community.